Scaled‐up manufacturing of recombinant antibodies produced by plant cells in a 200‐L orbitally‐shaken disposable bioreactor. Issue 2 (13th October 2014) - Raven, Nicole; Rasche, Stefan; Kuehn, Christoph; Anderlei, Tibor; Klöckner, Wolf; Schuster, Flora; Henquet, Maurice; Bosch, Dirk; Büchs, Jochen; Fischer, Rainer; Schillberg, Stefan
ABSTRACT Tobacco BY‐2 cells have emerged as a promising platform for the manufacture of biopharmaceutical proteins, offering efficient protein secretion, favourable growth characteristics and cultivation in containment under a controlled environment. The cultivation of BY‐2 cells in disposable bioreactors is a useful alternative to conventional stainless steel stirred‐tank reactors, and orbitally‐shaken bioreactors could provide further advantages such as simple bag geometry, scalability and predictable process settings. We carried out a scale‐up study, using a 200‐L orbitally‐shaken bioreactor holding disposable bags, and BY‐2 cells producing the human monoclonal antibody M12. We found that cell growth and recombinant protein accumulation were comparable to standard shake flask cultivation, despite a 200‐fold difference in cultivation volume. Final cell fresh weights of 300–387 g/L and M12 yields of ∼20 mg/L were achieved with both cultivation methods. Furthermore, we established an efficient downstream process for the recovery of M12 from the culture broth. The viscous spent medium prevented clarification using filtration devices, but we used expanded bed adsorption (EBA) chromatography with SP Sepharose as an alternative for the efficient capture of the M12 antibody. EBA was introduced as an initial purification step prior to protein A affinity chromatography, resulting in an overall M12 recovery of 75–85% and a purity of >95%. Our results demonstrate the suitability of orbitally‐shaken bioreactors for the scaled‐up cultivation of plant cell suspension cultures and provide a strategy for the efficient purification of antibodies from the BY‐2 culture medium. Biotechnol. Bioeng. 2015;112: 308–321. © 2014 Wiley Periodicals, Inc.